Analysis of the Effect Composite Exhaust Silincer Models Using Banana Stem Fiber on the Engine Power of the Toyota Kijang 7K Car - Aladin Eko Purkuncoro; Julianus Hutabarat; ‪Eko Budi Santoso‬ (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2022)
Along with the development of the technological era, human needs are also increasing. In addition, environmental problems also arise such as air pollution, sound/noise. Composite materials are expected to be used to become exhaust materials, of course as a solution to prove that the composite materials are able to reduce noise. The purpose of this study was to determine the power of exhaust engines made from composite materials, to determine the effect of composite exhaust on the power contained in the car. The data collection method used in this study is the observation method and literature study, namely by testing using a dynamometer and the engine used is the Toyota Kijang 7K type. From the data analysis of the relationship between engine speed (rpm) and engine power (HP), it can be concluded that the higher the rpm used, the more horse power will be affected. The urgency of this research includes making a composite exhaust, conducting power testing using a dynotest, the car that will be used for testing is a Toyota Kijang 7K type composite exhaust, and the cylinder models used are cylinder 1 model, cylinder 2 model, and cylinder model 3.